2011
DOI: 10.1093/hmg/ddr289
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation can adversely affect murine neural tube closure and embryonic survival

Abstract: Neural tube defects (NTDs), a common birth defect in humans, result from the failure of the embryonic neural tube (NT) to close properly. NT closure is a complex, poorly understood morphogenetic process influenced by genes and environment. The most effective environmental influence in decreasing the risk for NTDs is folic acid (FA) fortification and supplementation, and these findings led to the recommendation of periconceptual FA intake and mandatory fortification of the US grain supply in 1998. To explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 18 publications
3
87
1
Order By: Relevance
“…To block Rock binding to Shroom3, a single missense ) that lies within a short critical sequence known to associate with Rock1 (Mohan et al, 2012). Furthermore, this exact same missense mutation causes severe morphogenetic defects that are similar to those found in mice with a germline deletion of Shroom3 (Marean et al, 2011;Massarwa and Niswander, 2013). When Shroom3 R1838C was expressed in A431D cells that express N-cadherin wt , it was effectively recruited to the junctions (Fig.…”
Section: P120-catenin Is Required For Shroom3-dependent Acmentioning
confidence: 92%
“…To block Rock binding to Shroom3, a single missense ) that lies within a short critical sequence known to associate with Rock1 (Mohan et al, 2012). Furthermore, this exact same missense mutation causes severe morphogenetic defects that are similar to those found in mice with a germline deletion of Shroom3 (Marean et al, 2011;Massarwa and Niswander, 2013). When Shroom3 R1838C was expressed in A431D cells that express N-cadherin wt , it was effectively recruited to the junctions (Fig.…”
Section: P120-catenin Is Required For Shroom3-dependent Acmentioning
confidence: 92%
“…Therefore several reports support the hypothesis that folic acid likely acts through diverse mechanisms to influence neural tube closure (Li et al, 2011;Marean et al, 2011) so in future it will be of interest to determine the mechanistic basis of the specific gene-environment interactions that together influence neural tube closure.…”
Section: Role Of Folic Acid In Ntd Pathophysiologymentioning
confidence: 99%
“…Moreover, mouse NTD models have the potential to aid in understanding the genetics underlying folic acid responsiveness or nonresponsiveness in NTD prevention (Harris, 2009). Recently Marean et al, 2011 suggested that the response to folic acid supplementation may be more complex. They report that depending on the gene mutation, folic acid supplementation may adversely influence embryonic development and neural tube closure and thus the genetics of an individual may determine whether FA provides a beneficial outcome.…”
Section: Role Of Folic Acid In Ntd Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…wikispaces.com/). Her work has also addressed the influence of environmental factors, unexpectedly revealing that folic acid supplements in NTD mouse mutants can worsen their defects (Marean et al, 2011). This raises questions about the general recommendation of folic acid supplementation during pregnancy.…”
Section: Shaping the Neural Tubementioning
confidence: 99%